1972
DOI: 10.1037/h0033180
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in the person who will never produce anything original and useful: The concept of creativity as a normally distributed trait.

Abstract: HE term creativity is used with something approaching gay abandon by both psychologists (Yamamoto, 1965) and people in general (Bruner, 1962;Morreale, 1969), but is most appropriately applied where there is evidence of achievements that are original and make a meaningful contribution to culture. Writers on creativity would surely agree that if the term is to be applied to people who in the strict sense are not creative, the links between these and eminent creators must be established clearly. However, these li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
4

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(44 citation statements)
references
References 76 publications
2
38
0
4
Order By: Relevance
“…Others (e.g. Nicholls, 1972) supported Thurstone's definition, adding that creative abilities are found to some extent in nearly everyone (and thus offer at least the potential for being developed or encouraged), and that creativity is determined by what is new for the individual rather than society as a whole.…”
Section: Creativitymentioning
confidence: 93%
See 1 more Smart Citation
“…Others (e.g. Nicholls, 1972) supported Thurstone's definition, adding that creative abilities are found to some extent in nearly everyone (and thus offer at least the potential for being developed or encouraged), and that creativity is determined by what is new for the individual rather than society as a whole.…”
Section: Creativitymentioning
confidence: 93%
“…Solving problems with no previously learned solution and prior experience is defined as a feature of creative people (Nicholls, 1972;Mayer, 1989;Parkhurst, 1999;Torrance & Goff, 1989). According to Capretz and Ahmed (2010) and Myers et al (1998), sensors dislike problems unless their prior experience helps them solve the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some studies suggested that divergent thinking should not be identified as creative thinking (e.g. Nicholls, 1972).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Whilst many studies use divergent thinking tests to measure creativity (e.g. Martindale & Dailey, 1996), this method has been criticized for not fully capturing the concept (Sternberg & Lubart, 1996;Nicholls, 1972). However, more recent work stipulates that divergent thinking tests are predictors of creativity rather than synonymous to it (Runco, 2006).…”
mentioning
confidence: 99%